EVALUASI PROSES PEROLEHAN SURAT IJIN MENGEMUDI (SIM D) BAGI PENYANDANG CACAT DI KABUPATEN SIDOARJO - Bagus Aji Kuncoro; Wiwik Widayati; D Ghulam Manar (Journal of Politic and Government Studies, 2014)
ABSTRACTGoals to be achieved by this research are: 1) analyze and identify the process of obtaining a driver's license (SIM D) for Persons with Disabilities in Sidoarjo, 2) analyze and identify bottlenecks in the acquisition of a driver's license (SIM D) for the Disabled in Sidoarjo district, and 3) analyze and identify solutions to overcome barriers to government acquisition of a driver's license (SIM D) for Persons with Disabilities in Sidoarjo. The results of this study are expected to provide a foundation for further studies related to the regulatory process with disabilities in obtaining a driver's license.This is a descriptive qualitative research is to gain a clearer picture of the provision of regulatory processes with disabilities in obtaining a driver's license in Sidoarjo East Java. Technical data collection was done by using interviews and observations through the regulatory process with disabilities in obtaining a driver's license in Sidoarjo East Java. The results of the data collection so that the reduction is then performed relevant news and used as needed, then do the presentation by quoting that meet the rules of scientific writing (not the language of journalism), then do the analysis, and finally draw a statement to answer the problem.Based on the survey results revealed that: 1) The process of acquiring a driver's license (SIM D) for Persons with Disabilities in Sidoarjo relatively similar to the general driver's license, 2) barriers encountered by people with disabilities in obtaining a driver's license is the differences in perception among officers police in providing a driver's license to the applicant, and 3) the government until now has not been able to provide solutions related to the need for a driver's license for persons with disabilities. Attention of the government not to increase the knowledge, skills , independence, ability, willingness and competitiveness with disabilities. Government attention to people with disabilities are more mercy (charity).Keywords : regulations, driver's license, disabled.